Employment and the welfare state: A continental dilemma - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 1997)
Estimates of the comparative health of the North Americanand Western European economies and societies have had their fashion cycles -from Servain-Schreiber's warnings that Europe was falling behind, rather thancatching up with, American technological leadership in the 1960s, to Europeanexasperation over American trade and budget deficits in the 1970s, to anxietiesover Eurosclerosis in the early 1980s and over the American loss ofinternational competitiveness in the late 1980s. Presently, by all accounts, thesick man is again Europe, with higher unemployment and much lower rates of jobcreation over the last two decades or so. The main problem is a rising level oflong-term unemployment that mainly affects unskilled workers and, in mostcountries, young job seekers with low levels of schooling.
Keywords: 300